Diagnóstico laboratorial de dengue e leptospirose em pacientes com síndrome febril aguda - Bezerra, Laiane Fernanda de Melo (2012)
Among the arboviruses, dengue is the most important, constituting a serious public health problem worldwide. The tropical and subtropical regions are most affected, occurring approximately 100 million infections per year. The main symptoms that characterize the infection are fever, headache, retro-orbital pain, myalgia, arthralgia, prostration and rash. However, other infections have very similar symptoms to dengue, such as leptospirosis. Both dengue and leptospirosis, can cause outbreaks during the rainy seasons, since it is the best period for the dissemination of Aedes aegypti and contamination of wetlands by Leptospira sp.. This study aimed to employ different methods for the laboratory diagnosis of dengue and leptospirosis in patients with febrile syndrome. Eighty-six samples of 86 patients suspected of being infected with dengue were analyzed by NS1 immunoassay, NS1-ELISA, immunoassay IgM and IgG capture, IgM-ELISA and RT-PCR. Among the 86 patients evaluated, 48 (55.8%) were positive for at least one of diagnostic tests. After tested for dengue, 68 patients were evaluated by immunoassay IgM capture and by ELISA-IgM, both for identification of anti-Leptospira. Five (7.3%) were positive for this infection. It is very important to search for other infectious causes, such as leptospirosis, which is also a febrile illness, in patients with clinical suspicion of dengue, since the control of diseases prevalent only becomes possible when we know the infectious agents responsible for them. Therefore, it is necessary to use specific diagnoses for each infection, allowing epidemiological control programs can be carried out.